Small for Gestational Age Preterm Neonates Exhibit Defective GH/IGF1 Signaling Pathway - Emmanuelle Motte-Signoret; Emmanuelle Motte-Signoret; Emmanuelle Motte-Signoret; Shivani Shankar-Aguilera; Sylvie Brailly-Tabard; Yohan Soreze; Valentina Dell Orto; Rafik Ben Ammar; Daniele De Luca; Pascal Boileau; Pascal Boileau (Frontiers Media S.A., 2021)
Objective: To investigate the impact of fetal growth restriction (FGR) on hormonal regulation of post-natal growth and glucose metabolism [via insulin and growth hormone (GH)/Insulin-like Growth factor 1 (IGF1) axis pathways] in small for gestational age (SGA) neonates.Methods: We conducted a monocentric observational prospective comparative study on 73 singleton babies born with a weight inferior to 2,000 g. We analyzed auxological (weight, height and head circumference), and hormonal (GH, IGF1, and insulin plasma concentrations) data comparing SGA and appropriate for gestational age (AGA) neonates, between day 1 and 60.Results: One third (23/73) of the neonates were SGA. Twenty-five percent (18/73) required insulin for idiopathic hyperglycemia of prematurity and were smaller in weight and head circumference at discharge. In the SGA group compared with the AGA group, GH plasma concentrations were higher at day 3 (70.1 vs. 38.0 mIU/L) and IGF1 plasma concentrations were higher at day 10 (29.0 vs. 18.7 ng/ml).Conclusions: SGA neonates displayed resistance to GH and IGF1, concomitant to insulin resistance. This could partially explain the initial defective catch-up growth and, later in life, the higher prevalence of metabolic syndrome in this population.